2012
DOI: 10.12816/0002248
|View full text |Cite
|
Sign up to set email alerts
|

Factors Responsible for Making Consumer Attitude towards Islamic Banking : A Study of Islamic Banks Accountholders of Peshawar Region Pakistan

Abstract: The issue of bank interest is always a question mark for Muslims world. Does religion is the only factor which make consumer attitude towards Islamic banking? To find the very same issue that what factors are influencing consumers attitude towards Islamic banking, this research is conducted. There are many variables which create consumer attitude towards Islamic banking. These variables include Quality Service, Religious Support, Social Influence, Cost Effective, Awareness, and Availability. But it is importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…Subhani et al (2012) found that high profit, low service charges, religious motives, and quality of service were the most valued factors for the selection of an Islamic bank in Karachi. In Peshawar, religious support and quality of service are the most influential drivers of clients' attitudes towards IB (Khan, 2012). On the same note, religious motives, convenience, customer service quality and knowledgeable personnel are major determinants for full-fledged Islamic banks in Pakistan (Abdul Rehman and Masood, 2012).…”
Section: Ib Selection Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subhani et al (2012) found that high profit, low service charges, religious motives, and quality of service were the most valued factors for the selection of an Islamic bank in Karachi. In Peshawar, religious support and quality of service are the most influential drivers of clients' attitudes towards IB (Khan, 2012). On the same note, religious motives, convenience, customer service quality and knowledgeable personnel are major determinants for full-fledged Islamic banks in Pakistan (Abdul Rehman and Masood, 2012).…”
Section: Ib Selection Factorsmentioning
confidence: 99%
“…Convenience was measured using a six-item scale (Subhani et al, 2012;Ramdhony, 2013;Ramadan, 2013). WOM was measured using a four-item scale (Subhani et al, 2012;Khan, 2012;Ramdhony, 2013). Perceived value was measured using a four-item scale (Subhani et al, 2012;Khan, 2012;Ramdhony, 2013).…”
Section: Measurement Itemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Karena istilah ideologi agama mempunyai titik sensitifitas yang tinggi dibandingkan dengan istilah-istilah pelayanan maupun keunggulan kompetitif lainnya. Tentunya ada beberapa faktor lainnya untuk memmempengaruhi sikap dan prilaku masyarakat dalam menaggapi perbankkan syariah, Nazir Imtiaz (2013) mengungkapkan ada dua faktor yang mempengaruhi sikap masyarakat terhadap perbankkan syariah di Pakistan, yaitu faktor keagamaan dan faktor pengetahuan tentang perbankkan syariah, dari penelitiannya faktor yang sangat berpengaruh dalam perilaku masyarakat terhadap perbankkan syariah adalah faktor keagamaan (ideologi keagamaan) karena mereka memiliki keyakinan yang kuat tentang kepercayaan keimanannya yang diimplikasikan terhadap prilakunya kepada sistem ekonomi, penelitian ini juga ditegaskan oleh Muhammad Mazhar Manzoor, at al (2010) yang menyatakan bahwa faktor agama mempunyai peran dominan dalam memotivasi masyarakat terhadap perbankkan syariah sementara faktor ekonomi dan faktor sosial tidak bisa mengungguli kontribusi faktor agama yang sangat besar.Namun menurut Shahzad Khan (2012) bukan hanya faktor agama saja yang dominan dalam mempengaruhi sikap dan motivasi umat Muslim terhadap perbankan syariah, faktor kualitas pelayanan juga mempunyai pengaruh yang signifikan dibandingkan dengan pengaruh faktor sosial, dapat kita duga bahwa faktor keagamaan dan faktor kualitas pelayanan mempunyai pengaruh yang dominan terhadap keputusan umat Muslim untuk memilih perbankan syariah.…”
Section: Pendahuluanunclassified